Transforming Children’s Songs Into Islamic-Themed Songs As A Model Of Quran-Hadith Teaching In Indonesia - Putra, D.I. Ansusa; Nurmanda Sari, Fiqi; Chan, Sukma Sari Dewi; Mekki Klaina (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
Religious instruction in early childhood education faces growing challenges amid digital distractions and multicultural influences, necessitating creative and contextually relevant pedagogical strategies. This study aims to analyze the practice of modifying popular children's songs into Islamic songs as a contemporary method for teaching Quran and Hadith to early childhood learners in Indonesia. A qualitative descriptive method was employed, with data collected through classroom observations, in-depth interviews with 12 teachers, 2 parents and lyrical analysis of Islamic songs used across five Islamic early childhood education institutions Raudhatul Athfal (RA) and Taman Kanak-Kanak Islam Terpadu (TKIT) in Jambi City. The findings reveal that song modification effectively internalizes Quranic values and Hadith-based moral teachings in a playful and engaging manner. Notably, 10 out of 12 teachers and 2 parents reported significant improvements in children's attention spans and memorization of short Quranic verses and prophetic sayings, alongside observable positive behavioral changes. This method also fosters educator creativity in integrating Islamic content with local cultural expressions, producing a contextual and inclusive learning environment. Unlike previous studies that focus predominantly on conventional recitation-based approaches, this study demonstrates that adapting familiar melodies to Islamic themes offers a practical and replicable solution to declining engagement in Quran-Hadith learning at the foundational level. This study contributes to the field of Islamic early childhood pedagogy by providing an evidence-based model that harmonizes spiritual objectives with contemporary educational practices.